A Comparison of Finite Difference Schemes for Computational Modelling of Biosensors - Gaidamauskaitė, E.; Baronas, R. (Nonlinear Analysis: Modelling and Control, 2007)
This paper presents a one-dimensional-in-space mathematical model of an amperometric biosensor. The model is based on the reaction-diffusion equations containing a non-linear term related to Michaelis-Menten kinetics of the enzymatic reactions. The stated problem is solved numerically by applying the finite difference method. Several types of finite difference schemes are used. The numerical results for the schemes and couple mathematical software packages are compared and verified against known analytical solutions. Calculation results are compared in terms of the precision and computation time.
Keywords: numerical simulation; finite difference; reaction-diffusion; amperometric biosensor